Thematic and Structural Unity of Q 79 (al-Nazi'at): An Intratextual and Intertextual Analysis - Ahmad, Hamdi Putra (Universitas Muhammadiyah Surakarta, 2025)
This article will examine a variety of topics within QS. al-Nāzi'āt (79), such as the sura's word choices and linguistic characteristics, its structure and literary forms, its place in the Qur'an chronologically, its similarities to other suras from the same period of revelation in terms of phraseology, theme, and formality, its intertextual connections to some earlier traditions, and an analysis of any possible later redactional intervention. This article argues the sura's intratextual connections among its verses make it evident that all of its sections and subsections are interwoven with one another, proven by the tripartite structure that it has, the main theme of the sura, rhyme changes, and the occurrences of some unique phrases that mark the transition between sub-sections. Furthermore, QS. al-Nāzi'āt's intertextual links to previous traditions may have helped the first audience in the context of the sura's revelation better understand its core lessons, given their familiarity with ancient Arabic and Judeo-Christian literature. Finally, it is unlikely that verse 33 should be a later redactional intervention (as Angelika Neuwirth has contended) because some intratextual analysis of the sura reveals the opposite.